PIGEONS WITH BETTER BODY CONDITION DO NOT HAVE DIFFERENT SYMMETRIES - Parés-Casanova, Pere M. (2014)
Twenty seven homing pigeons (10 males and 17 females) were biometrically studied and the bilateral symmetry (right-left) level was evaluated. Analysed traits were the length of outer external rectrices, length of the wing and length of the second primary feather. The aim of the study was to check whether there is a relationship between the degree of asymmetry level and general health of the birds (expressed as a measure of body condition). Measurements showed a normal distribution and without differences according to the body condition, indicating a high degree of stable growth.